PROMOTION OF CLEAN AND HEALTHY LIVING HABITS PREVENT THE SPREAD OF THE COVID-19 CONTAGIOUS DISEASE IN PACAR KEMBANG VILLAGE, SURABAYA - Hanik Endang Nihayati; Tintin Sukartini; Rizki Fitryasari (Universitas Airlangga, 2021)
Introduction: The increase in the spread of disease due to the Covid-19 virus is the impact of low hygiene and healthy living habits in the community.Methods: Health promotion activities for clean and healthy living habits are carried out in the form of training in the area of RW 5, Pacarkembang Village, Surabaya City. This activity was attended by 40 housewives for 3 months, starting from July to September 2020. The material provided was about the importance of PHBS in households to prevent transmission of COVID 19 to evaluation of the habituation of implementing PHBS to prevent infectious disease COVID 19. The method used in activities are lectures, discussions, simulations and demonstrations by the facilitator as well as redemonstrations by the participants.Results: Knowledge, attitudes and psychomotor of housewives in the spread of Covid-19 transmission after being given PHBS training for 3 months increased. Assessment is carried out by comparing the pre-test and post-test results of the training participants. After attending the training, the majority of the participants' abilities were in the good category in the knowledge aspect (90%), the attitude aspect (90%) and the psychomotor aspect (87.5%).Conclusion: Increasing knowledge about Covid-19 during the training raises awareness, interest in housewives in Pacarakembang Village, Surabaya City to try and make behaviors to prevent the spread of Covid-19 a new good and healthy habit.